Tell Them I Said No. - Herbert, Martin (Berlijn : Sternberg Press, 2016)
Bacher, Lutz ; Hammons, David ; Martin, Agnes ; Noland, Cady ; Parsons, Laurie ; Posenenske, Charlotte ; York, Albert
Essays over kunstenaars die zich terugtrokken uit de kunstwereld
boek